Border porosities : movements of people, objects, and ideas in the Southern Balkans - Dimova, Rozita (Rethinking borders., 2021)
By drawing on geology's approaches to studying porosity, the book takes an innovative approach arguing that similarly to rocks and minerals that only appear solid and impermeable, seemingly impenetrable borders are inevitably traversed by different forms of passage.